READING A PRIMARY OCCURRENCE IN COMMUNICATION DEVELOPMENT IN THE FOREIGN LANGUAGE - Breshani, Alma (European Scientific Journal, ESJ, 2014)
Reading & understanding a text means being able to spot the ideas in it; to understand the given knowledge in order to compare them with the previous ones; to imply; to notice what is important, to split the known from the unknown in order to make use of ones knowledge. Readability is on the same rank with usability. Lexical knowledge and background make up two of the most essential elements that define the readability of a text. Precise reading, different techniques to ease its understanding has continuously changed especially in these years when its understanding is measured through testing. Reading comprehension development phases from analyses to synthesis enable you to deepen its study. In the long run, this study passed from a simple reading without defining objective to the one with measurable objective. Deepening the study for reading, increase its importance in a general communication in foreign language. Its complexity in many areas, affects not only the actors that play inside a class but also even the ones outside it.